Pengaruh Gaya Kepemimpinan Direktif, Supportif Dan Partisipatif Terhadap Kinerja Pegawai Di Dinas Pendidikan Kabupaten Tuban - Dwi Ihsani Mahendra Putra; Muhammad Ridwan Basalamah; Rahmawati Rahmawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to determine the influence of directive, supportive, and participatory leadership styles in a discrete and simultaneous manner related to the activities of workers in the Tuban Education Office. This type of study is a quantitative study. This study was carried out at the Tuban Region Education Office, which is located on Jl. Dr. Wahidin Sudirohusodo Number 875 Tuban, East Java Province. The community that was targeted in this study was the working group located at the Tuban Region Education Office, which consisted of 91 people. The basic information applied in this study comes from primary and secondary information. The information that has been obtained will be analyzed with SPSS version 20. Based on the study carried out related to the impact of the Directive, Supportive and Participatory leadership style with the Worker Activities of the Tuban Region Education Office, several conclusions can be drawn as follows: (1) The directive leadership style has a partial impact good and increases when confronted with the activities of the Tuban District Education Office workers, (2) The supporting leadership style separately has a good impact and increases related to the activities of the Tuban Region Education Office workers, (3) The leadership style participates separately has a good impact and causes improvements related to the activities of the Tuban Region Education Office workers, and (4) The directive, supportive, and spontaneous leadership styles that simultaneously and simultaneously have a good impact and lead to improvements related to the activities of the Tuban Region Education Office workers. Keywords : Leadership Style, Employee Performance.